2008
DOI: 10.1146/annurev.micro.61.080706.093323
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Release on the Ribosome: Mechanism and Implications for Translational Control

Abstract: Peptide release, the reaction that hydrolyzes a completed protein from the peptidyl-tRNA upon completion of translation, is catalyzed in the active site of the large subunit of the ribosome and requires a class I release factor protein. The ribosome and release factor protein cooperate to accomplish two tasks: recognition of the stop codon and catalysis of peptidyl-tRNA hydrolysis. Although many fundamental questions remain, substantial progress has been made in the past several years. This review summarizes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
104
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(106 citation statements)
references
References 93 publications
2
104
0
Order By: Relevance
“…Because these synthetic tRNAs are identical in every aspect with the exception of the anticodon, it seems unlikely that they would exhibit different rates of eEF1-a GTP hydrolysis or a different induced conformational fit upon codon-anticodon base pairing at the ribosome A-site (Rodnina et al 2005;Youngman et al 2008). Rather, our results suggest that eukaryotic release factors, eRF1/eRF3, terminate translation more efficiently at the opal and ochre codons as opposed to the amber codons.…”
Section: Incorporation Of Nbd-labeled Cys Using Cys-derived Suppressomentioning
confidence: 71%
“…Because these synthetic tRNAs are identical in every aspect with the exception of the anticodon, it seems unlikely that they would exhibit different rates of eEF1-a GTP hydrolysis or a different induced conformational fit upon codon-anticodon base pairing at the ribosome A-site (Rodnina et al 2005;Youngman et al 2008). Rather, our results suggest that eukaryotic release factors, eRF1/eRF3, terminate translation more efficiently at the opal and ochre codons as opposed to the amber codons.…”
Section: Incorporation Of Nbd-labeled Cys Using Cys-derived Suppressomentioning
confidence: 71%
“…Stop codons are decoded by class 1 release factor proteins (RFs) that act as bifunctional molecules to recognize stop codons with high fidelity and release the growing polypeptide chain in a hydrolytic reaction. Although the bifunctional nature of class 1 RFs is conserved from bacteria to eukaryotes, distinct proteins have evolved in these domains of life to accomplish this task (Youngman et al 2008). In bacteria, two related proteins, RF1 and RF2, recognize the three stop codons with overlapping specificity (UAA is recognized by both factors, while RF1 is specific for UAG and RF2 for UGA); in eukaryotes, a single factor, eRF1, recognizes all three stop codons.…”
Section: Introductionmentioning
confidence: 99%
“…However, careful comparisons between the antibiotic-binding sites in ribosomes from the eubacterium D. Radiodurans and those from the archaeon H. marismortui highlighted a neat distinction in the nucleotide sequence and orientation, leading to substantial differences in macrolide binding modes [2,75,80]. Hence, it was concluded that although A2058 is the main macrolide binding 'anchor', it is not the sole nucleotide determining drug positioning and, therefore, effectiveness.…”
Section: To Be or Not To Be A Pathogen Modelmentioning
confidence: 99%
“…[1,2]) obtained after 20 years [3] of extensive systematic explorations of crystal growth, refinements of bacterial growth pathways [4], and ribosome separations (E. Zimmerman, data not shown) and requiring the development of innovative methodologies, such as bio-crystallography at cryogenic temperatures [5], and an unconventional use of multiheavy atom clusters [6][7][8][9]. Accompanied by advances in the cryo electron microscopy that revealed elements of ribosome's functional dynamics, e.g.…”
Section: Introductionmentioning
confidence: 99%